1997
DOI: 10.1038/ng1097-179
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal lethality with kidney and pancreas defects in mice with a targetted Pkd1 mutation

Abstract: PKD1 is the most common site for mutations in human autosomal dominant polycystic kidney disease (ADPKD). ADPKD is characterized by progressive replacement of kidney tissue by epithelial cysts and eventual renal failure. Hepatic and pancreatic cysts are also common. The PKD1 protein, polycystin, is a cell-surface protein of unknown function that is widely expressed in epithelia and in vascular smooth muscle and myocardium. None of the genetic forms of murine polycystic disease map to the murine Pkd1 locus. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
287
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(319 citation statements)
references
References 11 publications
28
287
0
4
Order By: Relevance
“…Apart from the study of Griffin et al 27 that observed no polycystin-1 expression in the adult, this later distal expression pattern persisting into adult life has been observed in several other studies. 20,28,29 The expression of the ADPKD proteins appears only weakly in the earliest nephrogenic precursors, and is consistent with data from the Pkd1 Ϫ/Ϫ knockout mouse, 30 where formation of the nephron appears to occur normally; the role of these proteins is thus probably in tubular elongation and the maintenance of tubular architecture rather than in epithelial induction.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Apart from the study of Griffin et al 27 that observed no polycystin-1 expression in the adult, this later distal expression pattern persisting into adult life has been observed in several other studies. 20,28,29 The expression of the ADPKD proteins appears only weakly in the earliest nephrogenic precursors, and is consistent with data from the Pkd1 Ϫ/Ϫ knockout mouse, 30 where formation of the nephron appears to occur normally; the role of these proteins is thus probably in tubular elongation and the maintenance of tubular architecture rather than in epithelial induction.…”
Section: Discussionsupporting
confidence: 70%
“…It will be interesting to see if there is a neural phenotype in a fuller description of the Pkd1 Ϫ/Ϫ and Pkd2 Ϫ/Ϫ knockout mice. 19,30 One clear phenotype affecting the brain and associated with ADPKD, is an increased level of intracranial aneurysms. Interestingly, we found staining for both ADPKD proteins in the endothelial and smooth muscle cells of the arteries in the brain and other organs.…”
Section: Discussionmentioning
confidence: 99%
“…These cysts were only observed in Pkd1 knock-out mice but not in hypomorphic mice that have low levels of Pkd1 gene expression, suggesting that total absence of Pkd1 is necessary to induce the formation of glomerular cysts. 10,11,15,17,43,44 How these cysts arise is not entirely clear. As Pkd1 is deleted in Bowman's capsule, the suggested mechanism that urinary tract infections lead to increased pressure in Bowman's space seems not very likely in SM22-Pkd1 del/del mice.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous Pkd1 and Pkd2 knock-out mice die in utero, around embryonic day 15, because of severe cystic disease, vascular defects and/or abnormalities of the placental labyrinth, whereas heterozygous Pkd1 knock-out mice showed minimal renal cyst formation in adulthood. 4,[10][11][12][13][14][15] Furthermore, we described a Pkd1 mouse (hypomorphic) model, with low expression of Pkd1 showing progressive polycystic kidney disease and aortic dissecting aneurysms, indicating that Pkd1 is implicated in the structural integrity and function of the vasculature. 16,17 In the hypomorphic Pkd1 nl,nl mice a very prominent media thickening was seen in most of the animals analyzed.…”
mentioning
confidence: 99%
“…À terme, l'apparition de ces kystes et leur progression conduisent à une insuffisance rénale terminale pour laquelle la dialyse ou la greffe sont les seules options thérapeutiques. Les kystes peuvent être observés au cours du développement embryonnaire dès E15,5 chez la souris, par exemple chez les mutants nuls Pkd1 [22]. À ce stade, le rein embryonnaire devient fonctionnel et commence à filtrer le sang, ce qui renforce l'idée selon laquelle le flux jouerait un rôle dans la progression des kystes.…”
Section: Nphp1-9unclassified